Gambaran Penyebab Balita Stunting di Desa Lokus Stunting Kabupaten Pati - Aeda Ernawati (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2020)
ENGLISHStunting is still one of the health problems faced by Pati Regency. There are 12 Stunting Locus Villages in Pati District. The research objective was to describe the causes of stunting in the stunting locus village, Pati Regency. The research was conducted with a quantitative descriptive approach. The research was conducted in March-August 2020. The study population was all stunting toddlers in 12 Locus Stunting Villages. The research sample was all stunting toddlers in 10 stunting locus villages totaling 69 toddlers. The data used are secondary data from the Puskesmas. Data were analyzed descriptively. The results showed that the causes of stunting in the locus of stunting villages in Pati District were: 1) inadequate intake; 2) inadequate parenting; 3) low parental height; 4) not getting exclusive breastfeeding; 5) not getting early initiation of breastfeeding; 6) lack of environmental sanitation; 7) LBW; 8) Mother during pregnancy has anemia. Stunting was not caused by a single factor, but a combination of several causes. Therefore, all components of society should cooperate in order to reduce stunting cases. INDONESIAStunting masih menjadi salah satu masalah kesehatan yang dihadapi Kabupaten Pati. Ada 12 Desa lokus Stunting di Kabupaten Pati. Tujuan penelitian untuk menggambarkan penyebab stunting di desa lokus stunting Kabupaten Pati. Penelitian dilakukan dengan pendekatan deskriptif kuantitatif. Penelitian dilaksanakan bulan Maret-Agustus 2020. Populasi penelitian adalah semua balita stunting di 12 Desa Lokus Stunting. Sampel penelitian adalah semua balita stunting di 10 desa lokus stunting berjumlah 69 balita. Data yang digunakan yaitu data sekunder dari Puskesmas. Data dianalisis secara deskriptif. Hasil penelitan menunjukkan bahwa penyebab stunting di desa lokus stunting di Kabupaten Pati adalah adalah: 1) kurangnya asupan makanan; 2) pola asuh yang kurang memadai; 3) keturunan pendek; 4) tidak mendapatkan ASI eksklusif; 5) tidak mendapatkan IMD; 6) sanitasi lingkungan yang kurang; 7) BBLR; 8) ibu saat hamil mengalami anemia. Penyebab stunting umumnya tidak berdiri sendiri, tetapi kombinasi dari beberapa penyebab stunting. Diperlukan kerja sama semua komponen masyarakat dalam upaya penurunan stunting.